Smart water solutions : examples of innovative, low-cost technologies for wells, pumps, storage, irrigation and water treatment - Netherlands Water Partnership (Royal Tropical Institute, 2006)
Low-cost water technologies can help poor rural families double or even triple their annual income. Inspirational examples included in this booklet include how to use sunlight to purify water, effective low-cost water filters, low-cost drip irrigation and locally produced hand pumps that are five times cheaper than imported pumps.